Ownership structure's effect on financial performance: An empirical analysis of Jordanian listed firms - Amneh Alkurdi; Amneh hamad; Hussam Thneibat; Mahmoud Elmarzouky (Cogent Business & Management, 2021)
This study aims to examine the impact of the ownership structure on firm performance in the Jordan. This study employed the multiple-regression model and fixed regression effect to analyse the data. The sample included all Jordanian first market firms listed on the Amman Stock Exchange (ASE) from 2012 to 2018. The paper's findings reveal a positive and significant relationship between institutional ownership and both accounting measure Return on Assets (ROA) and market measure Tobin's Q (TQ). Other ownership structure types, such as concentration of ownership, also affect ROA and TQ. While managerial ownership shows a negative relationship with ROA, but there is no association with TQ. This study has broad and comprehensive practical implications that are good for policymakers. On the one hand, it adds to the debate on agency theory from the ownership structure and firm's performance relationship. On the other hand, it helps the Jordanian Government formulate policies and regulations to strengthen corporate governance (CG), which increases the interests of all stakeholders in the Jordanian market.
Keywords: 650; Ownership Structure; Financial performance; Emerging Markets; Return on Assets; Tobin’ s Q